The relationship between racial diversity and winning percentage: a study of men`s and women`s basketball teams and coaching staffs in the Atlantic Coast Conference from 2005-2009 - Bogar, C. T. (The Sport Journal, 2014)
Much attention has been devoted to the need for and importance of racial diversity in society. Studies have been conducted in business and industry which indicate that racial diversity is a positive attribute that contributes to success and positive performance. In intercollegiate athletics, racial diversity has been lauded as a desirable goal to be achieved (Chang, 1999; Cunningham and Fink, 2006).